Respuesta :

Answer:

Step-by-step explanation:

Table for function 1,

         x                      y              Difference 1          Difference 2        

         2                    10                      -                             -

         3                     1                 1 - 10 = -9                     -

         4                    10                10 - 1 = 9                9 - (-9) = 18

         5                    37               37 - 10 = 27            27 - 9 = 18

         6                    82               82 - 37 = 45          45 - 27 = 18

Since, difference 2 is common as 18,

Table will represent a quadratic function.

Table for function 2,

        x                    y               Difference 1            Difference 2

        5                    16                       -                               -

        6                    19              19 - 16 = 3                        -

        7                    28             28 - 19 = 9                  9 - 3 = 6

        8                    43             43 - 28 = 15              15 - 9 = 6

        9                    64             64 - 43 = 21              21 - 15 = 6

Since, difference 2 is common as 6,

Table will represent a quadratic function.

Table for function 3,

        x                    y                   Ratio

        1                   112                     -

        2                  56               56 ÷ 112 = [tex]\frac{1}{2}[/tex]  

        3                  28               28 ÷ 56 = [tex]\frac{1}{2}[/tex]

        4                   14               14 ÷ 28 = [tex]\frac{1}{2}[/tex]

        5                    7                7 ÷ 14 = [tex]\frac{1}{2}[/tex]

Since, ratio is common as [tex]\frac{1}{2}[/tex].

Table will represent an exponential function.